INHIBITORY EFFECT OF LYCOPENE AGAINST THE GROWTH OF HUMAN GASTRIC CANCER CELLS - Zhou, ShenKang; Zhang, RuiLi; Bi, TieNan; Lu, Yong; Jiang, LiangXian (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background The aim of this study was to investigate the anti-proliferative effect of Lycopene on HGC-27 cells.Materials and methods HGC-27 cells were treated with varying concentration lycopene for 24, 48, 72 h. The cell growth inhibitionwas analyzed by MTT. Western blotting was used to indicate changes in the levels of LC3-I, LC3-II, ERK (extracellularsignal‐regulated protein kinase) and phosphorylation-ERK (p-ERK).Results Lycopene displayed antiproliferative activity in HGC-27 cell lines. Western blotting showed that Lycopene significantlyenhanced LC3-I, p-ERK proteins expression. In gastric cancer nude mice model, lycopene treatment significantly decreased tumourweight. These findings indicated that lycopene treatment induces the anti-proliferation of HGC-27 cells.Conclusion Lycopene treatment inhibited HGC-27 cells growth by activating ERK.